2006
DOI: 10.1111/j.1399-3089.2006.00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of prolonged gene expression by Epstein–Barr virus‐based plasmid in porcine cells

Abstract: The EBV-based plasmid may be useful for genetically manipulating porcine cells to enhance their value as xenotransplantation sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In previous studies, Lipofectamine-mediated transfection of swine kidney epithelial cells with episomal vectors gave a 20e30% transfection yield [27], and FuGENE 6-mediated transfection of human embryonic stem cells with episomal vectors gave a 30e40% transfection yield [10]. In both of these cases, an immortalized cell line was used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, Lipofectamine-mediated transfection of swine kidney epithelial cells with episomal vectors gave a 20e30% transfection yield [27], and FuGENE 6-mediated transfection of human embryonic stem cells with episomal vectors gave a 30e40% transfection yield [10]. In both of these cases, an immortalized cell line was used.…”
Section: Discussionmentioning
confidence: 99%
“…While this method was successful in cancerous cell lines [10,27], there are no reports of successful delivery into primary cells obtained from fresh tissue. Therefore, in this study we have identified some potential commercial transfection reagentsdwhich are inexpensive, involve simple handling, and show low toxicity and immunogenicitydfor transport of episomal vectors into primary cells, and we evaluated their cytotoxicity and transfection efficiency.…”
Section: Introductionmentioning
confidence: 89%
“…Son et al. [22] investigated the mechanisms underlying the prolonged gene expression of Epstein–Barr virus (EBV)‐based plasmids, pEBV‐GFP, in porcine neonatal pancreatic cell clusters. They observed that the EBV‐based plasmids, pEBV‐GFP, remained as episome in transfected porcine cell clusters, rather than integrating into the chromosomal DNA.…”
Section: Gene Therapymentioning
confidence: 99%